Storybook ending : a novel - Macdonald, Moira (Dutton, 2025)
"A charming story about romance, friendship, and a love of books, in which two women-a lonely remote worker and a widowed single mom-and a handsome local bookstore clerk find themselves in an unusual love triangle when an anonymous note left in a book finds the wrong recipient"--